Given :-
To find :-
Solution :-
On writing equations mathematically ,
[tex]\red{\longrightarrow}[/tex] x(5 + k) = 3
[tex]\red{\longrightarrow}[/tex] x(3 - k) = 1
Divide these both equations ,
[tex]\red{\longrightarrow}[/tex] 5 + k/ 3 -k = 3/1
Cross multiply ,
[tex]\red{\longrightarrow}[/tex] 5 + k = 3(3 - k)
[tex]\red{\longrightarrow}[/tex] 5 + k = 9 - 3k
[tex]\red{\longrightarrow}[/tex] 4k = 4
[tex]\red{\longrightarrow}[/tex] k = 4/4
[tex]\red{\longrightarrow}[/tex] k = 1
On substituting the value of k ,
[tex]\red{\longrightarrow}[/tex] x = 3/(5 + k)
[tex]\red{\longrightarrow}[/tex] x = 3/ 5+1
[tex]\red{\longrightarrow}[/tex] x = 3/6
[tex]\red{\longrightarrow}[/tex] x = 1/2 = 0.5
Hence the required answer is 1/2.